시설물 안전 및 유지관리 성과 평가에 관한 연구 - 시설물 안전등급 변화를 중심으로 - 강상혁; 최석인; 김화랑; 이정석; Kang, Sanghyeok; Choi, Seok In; Kim, Hwarang; Lee, Jeongseok (한국건설관리학회 논문집, 17(2), 2016)
Recently, the paradigm shift of new construction into efficient operation and maintenance of infrastructure is seen. Also, concerns about infrastructure safety, especially the aged infrastructure, are on the increase. This study evaluates the current status of infrastructure safety and maintenance using data from 1994 to 2014 in Facility Management System operated by Korea Infrastructure Safety Corporation. Also, a quantitative analysis of safety performance of infrastructure is conducted to find out the enhancement of infrastructure safety in Korea. It was found that safety of facilities in Korea have been enhanced for the past decades. Improvement of safety performance of facilities is attributed to periodic safety inspection and repair and reinforcement. The result of the study can be used as a basic material for efficient and effective facility maintenance policies and strategies. 최근 인프라 투자는 신규 건설 중심에서 기 시공된 시설의 효율적인 운영과 유지관리로 패러다임이 전환되고 있다. 이와 함께 시설물 노후화에 따른 안전에 대한 국민적 관심이 증폭되고 있다. 본 연구에서는 한국시설안전공단의 시설물관리종합정보시스템에 등록되어 있는 1994년부터 2014년까지의 시설물 유지관리 관련 데이터를 바탕으로 점검진단지수와 보수보강지수 등의 정량적 분석 방법론을 적용하여 유지관리 활동의 성과를 평가하였다. 또한 과거에 비해 현재 시설물의 안전도가 어느 정도 향상되었는지 안전등급 데이터를 토대로 분석을 실시하였다. 분석 결과 우리나라 시설물의 안전성은 과거 대비 크게 향상된 것으로 나타났으며 안전성이 향상된 요인으로는 정기적인 안전점검과 그에 따른 보수 보강 활동의 결과로 추정해 볼 수 있다. 본 연구를 통해 도출 된 결과는 향후 시설물의 유지관리 정책 및 전략 수립에서 기초적 자료로 활용이 가능할 것으로 판단된다.